Health-related quality of life in patients with Rheumatoid Arthritis - Ferreira, Lara (2018)
Objectives: Rheumatoid arthritis (RA) is a chronic rheumatic disease of unknown aetiology and greater incidence among the elderly. It can lead to serious consequences regarding functional limitations and patient's ability to work. The purpose of this study was to assess the health-related quality of life in patients with RA. Methods: Portuguese version of SF-6D and Portuguese translations of EQ-5D and AIMS2-SF were self-administered in a postal survey to a representative sample of the Portuguese population with RA. Data concerning the patients' characteristics and the stage of the disease were also collected. Results: The majority of the patients presented minor problems in some of the instruments' dimensions. In a scale from 0.30 to 1.00, the average utility score was 0.77. The lowest utility scores were reported by women, those who were divorced or separated, individuals with lower educational levels, who had lower incomes, were recently diagnosed and those who were not taking new biological therapies. Apart from these, patients who had a more severe RA and co-morbidity also report lower utility scores. Conclusions: The preference-based utility measures used in this study adequately discriminate across different RA severity and socio-demographic background. Assuming that these values represent the patients' preferences and the utility associated with their health state, the results presented in this paper may be used as an approximation to normative values for the SF-6D in economic evaluation studies as well as in clinical studies.